ANALYSIS OF DIFFERENCES IN PERFORMANCE BANK BEFORE AND DURING THE COVID-19 PANDEMIC - Sufriyani Sufriyani; Lusianus Heronimus Sinyo Kelen (LPPM Politeknik Pratama, 2021)
The Corona Virus Disease 2019 pandemic (known as COVID-19) has hit all sectors and human life, including banking activities in Indonesia. The risk of banking as a company collecting public funds is also increasing due to the restrictions on community activities and the low level of the Indonesian economy after being hit by COVID-19. Bank Indonesia did not predict that such a condition would occur. Therefore, this study is aimed to examine the differences in Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Non Performing Loans (NPL), Loan to Deposit Ratio (LDR) in the go public banking sector in Indonesia before and after COVID-19. This study uses a quantitative approach using a non-parametric statistical test, the wilcoxon signed-rank test. This test is applied because the small number of samples and the data are not normally distributed. There are only 19 banks taken as samples and all are listed on the Indonesia Stock Exchange. The data is collected based on the financial statements of 2019 (conditions before COVID-19 occurred in Indonesia) and 2020. It can be concluded from the results of the analysis that CAR and BOPO do not show significant differences before and after COVID-19. However, NPL and LDR prove significant differences before and after COVID-19.